Impact of Financial Ratios on Strategic Investment Decisions: A Case Study of Petronas and Sapura Energy - Kamilah, Athia Nur; Fauziyah, Nur; Rinaima , Chetrine Alya; Utari , Septi (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
The use of financial ratio analysis as a decision-making tool is widely recognized. However, there is limited comparative research examining how such analysis influences investment assessment and strategic implications between financially stable and distressed companies in the same industry. This study aims to address that gap by evaluating and comparing the financial performance of Petroliam Nasional Berhad (PETRONAS) and Sapura Energy Berhad. A quantitative research method was employed, using profitability, liquidity, leverage, and investment valuation ratios derived from the companies’ annual financial statements. The results reveal a stark contrast between the two entities: PETRONAS exhibits strong profitability, high liquidity, balanced leverage, and favorable investment valuation, reflecting its resilience and capacity for sustainable growth. In contrast, Sapura Energy shows negative profitability, critical liquidity shortages, excessive leverage, and unfavorable investment valuation, indicating severe financial distress. These findings contribute to a better understanding of how financial health impacts strategic positioning and investment attractiveness in the energy sector. The study offers practical insights for investors, policymakers, and corporate managers in designing targeted strategies, such as energy transition initiatives and risk mitigation measures, to enhance competitiveness and long-term sustainability.